Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 17. Beitrag. Diptera: Bombyliidae. - Ionescu, M. A.; Weinberg, Medeea (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are summarized the Bombyliidae known from Albania. The expedition to Albania of the Deutsches Entomologisches Institut collected 187 specimens of 27 species, 19 of which are new to the fauna of this country. Now 38 species of this family are known from Albania.